2020
DOI: 10.1001/jamaoncol.2020.2020
|View full text |Cite
|
Sign up to set email alerts
|

FOLFIRINOX for the Treatment of Advanced Gastroesophageal Cancers

Abstract: IMPORTANCE Standard first-line regimens for patients with metastatic gastroesophageal adenocarcinomas have an approximate 40% objective response rate (ORR). The combination of leucovorin, fluorouracil, irinotecan, and oxaliplatin (FOLFIRINOX) has been efficacious as first-line therapy for other gastrointestinal cancers, such as pancreatic and colon cancers.OBJECTIVE To evaluate the clinical activity and safety of FOLFIRINOX as first-line treatment for patients with advanced gastroesophageal adenocarcinoma. DES… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 52 publications
0
11
0
1
Order By: Relevance
“…The objective response rate (ORR) to FOLFOXIRI in these patients was 60%[ 5 ]. A phase II trial of FOLFIRINOX in patients with advanced gastroesophageal cancer showed an ORR of 61%[ 6 ]. This is in contrast to a response rate of only 31.6% in patients with metastatic PDAC receiving FOLFIRINOX[ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The objective response rate (ORR) to FOLFOXIRI in these patients was 60%[ 5 ]. A phase II trial of FOLFIRINOX in patients with advanced gastroesophageal cancer showed an ORR of 61%[ 6 ]. This is in contrast to a response rate of only 31.6% in patients with metastatic PDAC receiving FOLFIRINOX[ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…FLOT is now a standard of care peri‐operative treatment for gastric and gastroesophageal junction adenocarcinoma, and is increasingly used in patients with advanced disease 2,21 . Promising efficacy data have also been reported with the repurposing of FOLFIRINOX in the metastatic setting of gastroesophageal cancer 22 . As a result, the interest for modified DCF regimens has gradually reduced, this being further mitigated by the negative results of recent trials comparing DCF‐like regimens with standard doublet chemotherapy 23 …”
Section: Discussionmentioning
confidence: 99%
“… 2 , 21 Promising efficacy data have also been reported with the repurposing of FOLFIRINOX in the metastatic setting of gastroesophageal cancer. 22 As a result, the interest for modified DCF regimens has gradually reduced, this being further mitigated by the negative results of recent trials comparing DCF‐like regimens with standard doublet chemotherapy. 23 …”
Section: Discussionmentioning
confidence: 99%
“…In a recently published phase II trial of advanced GEA, among ERBB2-negative patients treated with FOLFIRINOX alone, the ORR was 61%, with a median overall survival of 15.5 months. Among ERBB2-positive patients treated with FOLFIRINOX and trastuzumab, the ORR was 85%, with a median OS 19.6 months 16 . Additionally, a multi-institutional phase II trial of 36 patients with locally advanced GEA evaluated pharmacogenomically dosed perioperative FOLFIRINOX and reported R0 resection rate of 92% and a pathologic complete response (pCR) rate of 23% 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Outside of GEA, FOLFIRINOX has emerged as a standard of care for pancreatic cancer in both the resectable and metastatic setting 13,14 . Additionally, there is a growing body of literature evaluating the e cacy of this regimen in gastroesophageal and gastric cancers [15][16][17] . A pooled analysis of two ongoing Phase II trials of FOLFIRINOX in the rst line metastatic setting for GE junction cancers demonstrated an overall response rate (ORR) of 62.5% 15 .…”
Section: Introductionmentioning
confidence: 99%